Preparation method of antistatic fabric based on Cu9S5 / organic matter double coating
By forming a Cu9S5/organic dual coating on the fabric, especially a conjugated Schiff base, polyaniline and polypyrrole coating, the problem of insufficient conductivity and antistatic properties of polyester and cotton fabrics is solved, achieving high-efficiency conductivity and antistatic properties of the fabric, and also possessing excellent UV protection properties.
Patent Information
- Application Number
- CN202411372738.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
Polyester and cotton fabrics are deficient in antistatic properties, and existing technologies are unable to effectively improve their conductivity and antistatic properties. Furthermore, there are difficulties in coating cotton fabrics with copper sulfides.
An in-situ preparation method is used to form a Cu9S5/organic double coating on the fabric, including a conjugated Schiff base, polyaniline and polypyrrole coating. A conductive layer is formed inside and on the surface of the fiber through chemical reaction, which improves the conductivity and antistatic properties of the fabric.
The prepared double-coated fabric achieves Class A antistatic performance, significantly reduces resistivity, and possesses excellent UV protection properties, meeting UV protection product standards.
Smart Images

Figure CN119287675A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile finishing, and in particular relates to a method for preparing an antistatic fabric based on a Cu9S5 / organic matter double coating. Background Art
[0002] Polyester fiber has become the most widely used and consumed fiber variety due to its advantages such as high modulus, high strength, good elasticity, excellent shape retention and heat resistance. However, polyester fiber also has some inherent limitations, such as poor moisture absorption and air permeability, difficulty in dyeing, hard hand feel, poor antistatic properties, etc. These shortcomings limit its application in the field of clothing. Polyester fabrics are prone to static electricity due to their poor moisture absorption and high resistivity. Cotton fabrics are widely used in clothing, household goods and industrial purposes due to their comfort, warmth retention, moisture absorption and air permeability, but they have disadvantages such as easy wrinkling, shrinkage, poor elasticity and easy mold. At present, how to improve the antistatic properties of polyester and cotton fabrics has attracted much attention.
[0003] Conductive polymers have received extensive attention since their discovery. Among various intrinsically conductive polymers, polyaniline has broad application prospects in the industrial field due to its good conductivity, easy synthesis, chemical stability, low cost and good thermal stability; polypyrrole is composed of pyrrole units, has good conductivity and chemical stability, and is widely used in conductive polymers, electronic devices and sensors. Polypyrrole is usually prepared by chemical synthesis or electrochemical polymerization, and its structure and properties can be regulated. It has a wide range of applications in traditional electronic and electrical fields.
[0004] Conjugated Schiff bases are a class of Schiff base compounds with a special chemical structure. Their main chain contains a two-dimensional planar structure with a large π bond, which is mainly connected by C=N double bonds. The electron cloud of this type of compound is evenly distributed and has a large degree of delocalization, so it has excellent electrical, optical and magnetic properties.
[0005] Sulfides of metals such as copper and silver have good electrical conductivity, and copper sulfide is the most commonly used. Through chemical reactions or grafting of other metal ions, the fibers are made conductive. However, cotton fabrics cannot be directly coated with copper sulfide. Copper pentasulfide (Cu9S5) has electrical conductivity and photoelectric properties, and has important application value in catalysis, electrochemical energy storage, and optoelectronic devices. Cu9S5 is usually prepared by chemical synthesis or precipitation, and its morphology and structure can be regulated to achieve specific functional properties.
[0006] Some studies have used metal oxides and conductive polymers for compounding, such as polypyrrole and manganese dioxide, to improve the conductivity of the base material through synergistic effects. However, MnO2 needs to be prepared at high temperatures, and the preparation process is complicated and expensive. Carbon-based nanomaterials such as carbon nanotubes, graphene, and MXene, etc., have large specific surface areas that increase the loading capacity of conductive polymers and improve the redox reaction ability of conductive polymers. However, carbon-based nanomaterials are prone to agglomeration. Therefore, further research is needed to improve the conductivity and antistatic properties of fabrics. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an antistatic fabric based on a Cu9S5 / organic double coating.
[0010] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0011] In-situ preparation of an organic coating on the fabric to obtain an organic single-coated fabric;
[0012] The copper sulfate solution and the sodium thiosulfate solution are mixed evenly to obtain a mixed solution Ⅰ;
[0013] The organic single-coated fabric is placed in the mixed solution I, and after constant temperature reaction, it is taken out, thoroughly washed, and dried to obtain the Cu9S5 / organic double-coated fabric;
[0014] Wherein, the organic coating includes one of a conjugated Schiff base coating, a polypyrrole coating and a polyaniline coating.
[0015] As a preferred solution of the method for preparing the antistatic fabric based on Cu9S5 / organic double coating of the present invention, the fabric comprises one of cotton fabric and polyester fabric.
[0016] As a preferred embodiment of the method for preparing the antistatic fabric based on Cu9S5 / organic double coating of the present invention, the method for preparing the conjugated Schiff base coating comprises:
[0017] The fabric pretreated with caustic soda solution is immersed in 0.01-0.09 mol / L p-phenylenediamine ethanol solution and reacted at 20-25° C. for 2-2.5 hours;
[0018] Add glyoxal solution of the same concentration as the p-phenylenediamine ethanol solution, stir evenly, and shake at 65-85° C. for 6-7 hours to form a conjugated Schiff base coating on the fabric.
[0019] As a preferred embodiment of the method for preparing the antistatic fabric with Cu9S5 / organic double coating of the present invention, the method for preparing the polyaniline coating comprises:
[0020] Aniline sulfuric acid solution with an aniline monomer concentration of 0.2 to 0.6 mol / L and ammonium persulfate solution with a concentration of 0.15 to 1.5 mol / L are mixed evenly;
[0021] When the solution starts to turn blue, add the fabric, control the bath ratio to 1:50-1:100, and shake at room temperature for 10-12 hours;
[0022] The fabric is taken out, thoroughly washed and dried, thereby forming a polyaniline coating on the fabric.
[0023] As a preferred embodiment of the method for preparing the antistatic fabric based on Cu9S5 / organic double coating of the present invention, the method for preparing the polypyrrole coating comprises:
[0024] The fabric was immersed in 0.3-0.36 mol / L FeCl3 solution and 0.3-0.36 mol / L sodium 5-sulfosalicylate solution and frozen for 30-50 min;
[0025] An equal volume of 0.25-0.55 mol / L cyclohexane solution of pyrrole monomer is added, and after the cyclohexane solution is frozen, it is kept statically at 0-5°C for 10-12 hours, then taken out, repeatedly washed with distilled water and ethanol, respectively, and vacuum dried to form a polypyrrole coating on the fabric.
[0026] As a preferred solution of the method for preparing the antistatic fabric based on Cu9S5 / organic double coating of the present invention, wherein: the pH value of the sulfuric acid is adjusted to 2-2.5.
[0027] As a preferred embodiment of the method for preparing the antistatic fabric based on Cu9S5 / organic double coating according to the present invention, the concentration of the copper sulfate solution is 3-9 g / L, and the concentration of the copper thiosulfate solution is 3.6-10.8 g / L.
[0028] As a preferred solution of the method for preparing the antistatic fabric based on Cu9S5 / organic double coating of the present invention, the reaction temperature of the isothermal reaction is 55-85°C, and the reaction time is 25-95min.
[0029] Another object of the present invention is to overcome the deficiencies in the prior art and provide an antistatic fabric based on a Cu9S5 / organic double coating prepared by the preparation method.
[0030] As a preferred embodiment of the antistatic fabric based on Cu9S5 / organic double coating described in the present invention, the Cu9S5 / organic double coating fabric prepared by the preparation method has a UPF value greater than 40, and a UVA transmittance less than 5%, and the antistatic performance reaches Class A.
[0031] Beneficial effects of the present invention:
[0032] (1) The double-coated fabric prepared by the present invention meets the requirements of UV protection products (UPF value is greater than 40, and UVA transmittance is less than 5%), and the antistatic performance reaches Class A.
[0033] (2) Cu9S5 synergizes with conjugated Schiff base, polyaniline and polypyrrole to improve the conductivity of cotton and polyester fabrics, improve the antistatic performance, flame retardant effect and UV protection performance, and achieve a higher weight gain rate of organic coating by optimizing the preparation conditions. A higher weight gain rate of Cu9S5 is achieved by optimizing the preparation conditions of Cu9S5.
[0034] (3) Aniline monomer is filled into and on the surface of cotton fabric by in-situ polymerization, and chemical oxidation polymerization reaction occurs inside and on the surface of the fiber. The cotton fiber with polyaniline coating reacts with copper sulfide to improve the conductivity of cotton fabric.
[0035] (4) By adopting the in-situ polymerization method, pyrrole is polymerized on the surface of cotton fabric to form a polypyrrole coating. The cotton fabric with the polypyrrole conductive layer undergoes a coordination reaction with copper sulfide, thereby preparing a composite conductive fabric with good conductivity, UV resistance, and antistatic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0037] Figure 1These are scanning electron microscope images of the original polyester fabric (a), the conjugated Schiff base single-coated polyester fabric (b), and the Cu9S5 / conjugated Schiff base double-coated polyester fabric (c) in Example 1 of the present invention.
[0038] Figure 2 This is the EDS image of the conjugated Schiff base single-coated polyester fabric in Example 1 of the present invention.
[0039] Figure 3 This is the EDS image of the Cu9S5 / conjugated Schiff base double-coated polyester fabric in Example 1 of the present invention.
[0040] Figure 4 These are the X-ray diffraction patterns of the original polyester fabric, the conjugated Schiff base single-coated polyester fabric, and the Cu9S5 / conjugated Schiff base double-coated polyester fabric in Example 1 of the present invention.
[0041] Figure 5 These are infrared spectra of the original polyester fabric, the conjugated Schiff base single-coated polyester fabric, and the Cu9S5 / conjugated Schiff base double-coated polyester fabric in Example 1 of the present invention.
[0042] Figure 6 These are scanning electron microscope images of the original cotton fabric, the polyaniline single-coated cotton fabric, and the Cu9S5 / polyaniline double-coated cotton fabric in Example 2 of the present invention, wherein the original cotton fabric (a)×10000, (a')×2500, the polyaniline single-coated cotton fabric (b)×2400, (b')×20000, and the Cu9S5 / polyaniline double-coated cotton fabric (c)×2400, (c')×20000.
[0043] Figure 7 This is the EDS image of the polyaniline single-coated cotton fabric in Comparative Example 2 of the present invention.
[0044] Figure 8 This is the EDS image of the Cu9S5 / polyaniline double-coated cotton fabric in Example 2 of the present invention.
[0045] Fig. 9 These are the XRD patterns of the original cotton fabric, the polyaniline single-coated cotton fabric, and the Cu9S5 / polyaniline double-coated cotton fabric in Example 2 of the present invention.
[0046] Fig.10 The infrared spectra of the original cotton fabric, the polyaniline single-coated cotton fabric, and the Cu9S5 / polyaniline double-coated cotton fabric in Example 2 of the present invention are shown.
[0047] Fig.11 These are infrared spectra of the original cotton fabric, the polypyrrole single-coated cotton fabric, and the Cu9S5 / polypyrrole double-coated cotton fabric in Example 3 of the present invention.
[0048] Fig.12These are the XRD patterns of the original cotton fabric, the polypyrrole single-coated cotton fabric, and the Cu9S5 / polypyrrole double-coated cotton fabric in Example 3 of the present invention.
[0049] Fig.13 These are scanning electron microscope images of the original cotton fabric, the polypyrrole single-coated cotton fabric, and the Cu9S5 / polypyrrole double-coated cotton fabric in Example 3 of the present invention, wherein the original cotton fabric (a)×10000, (a')×2500; the polypyrrole single-coated cotton fabric (b)×2400, (b')×20000; the Cu9S5 / polypyrrole double-coated cotton fabric (c)×2400, (c')×20000.
[0050] Fig.14 This is the EDS image of the Cu9S5 / polypyrrole double-coated cotton fabric in Example 3 of the present invention.
[0051] Fig.15 The graph is a weight gain-resistivity graph of the Cu9S5 / conjugated Schiff base double-coated polyester fabric in Example 1 of the present invention and Comparative Examples 6 and 7. DETAILED DESCRIPTION
[0052] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0053] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0054] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0055] The raw materials used in the present invention are all commercially available in the art unless otherwise specified. The cotton and polyester fabrics used in the present invention are from the Shanghai Textile Industry Technical Supervision Institute.
[0056] The weight gain rate of the fabric in the present invention is calculated according to the following formula.
[0057]
[0058] Where W1 is the weight of the fabric after reaction, W0 is the weight of the fabric before reaction, and W G is the weight gain rate (%).
[0059] The limiting oxygen index in the present invention is used to characterize the combustion effect of the material. According to GB / T 5455-2014, an intelligent oxygen index tester is used to test the limiting oxygen index of the sample.
[0060] The present invention adopts a universal tensile testing machine to test the strength of the sample, and the implementation standard is GB 13022-1991.
[0061] The breaking strength test of the original cotton fabric, the polyaniline single-coated fabric and the Cu9S5 / polyaniline double-coated cotton fabric in the present invention is carried out according to the test standard GB / T3923-1997. The fabrics are cut into strips with a length of 5 cm×1 cm. The thickness of the strips is measured three times with an electronic thickness gauge, and the average value is taken as the thickness of each strip. The thickness is measured twice on a fabric strength tester, and the average value is finally calculated.
[0062] The invention adopts a YG(B)912E textile anti-ultraviolet performance tester to test the anti-ultraviolet performance of fabrics, and measures the UVA, UVB and UPF of polyester fabrics according to GB / T18830-2009. The higher the UPF value, the better the anti-ultraviolet performance of the fabric. According to national standards, only when the UPF value of the sample is greater than 40 and the UVA transmittance is less than 5%, it is called an anti-ultraviolet product.
[0063] The present invention adopts a YG(B)342E fabric induction static tester and uses the standard GBT 12703.1 to test fibers with different coatings respectively, and compares and analyzes the static absorption performance of the coatings.
[0064] Example 1
[0065] This embodiment provides a method for preparing a Cu9S5 / conjugated Schiff base double-coated polyester fabric.
[0066] 1) Pretreatment of polyester fabric: caustic soda concentration is 10g / L, bath ratio is 1:50, react at 80°C for 15min, take out and wash thoroughly, dry and set aside.
[0067] 2) Preparation of conjugated Schiff base coating:
[0068] After fully dissolving p-phenylenediamine in 100 ml of ethanol solution, a p-phenylenediamine ethanol solution with a p-phenylenediamine concentration of 0.03 mol / L is obtained;
[0069] The pretreated polyester fiber was immersed in a p-phenylenediamine ethanol solution and reacted at room temperature for 2 hours;
[0070] The same concentration of glyoxal solution (0.03 mol / L) was added and stirred evenly, and then placed in a constant temperature shaking water bath at 75° C. and continued to shake for 6 hours to obtain a conjugated Schiff base single-coated polyester fabric.
[0071] 3) Preparation of Cu9S5 coating:
[0072] The conjugated Schiff base single-coated polyester fabric was placed in a mixed solution of copper sulfate and sodium thiosulfate with concentrations of 6 g / L and 7.2 g / L respectively, the pH value of the solution was adjusted to 2 with sulfuric acid, the bath ratio was controlled to be 1:80, the reaction temperature was 65°C, and the constant temperature was shaken for 65 minutes to obtain the Cu9S5 / conjugated Schiff base double-coated polyester fabric.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 1 is that step 3) is omitted, and the remaining steps are referred to Example 1 to prepare a conjugated Schiff base single-coated polyester fabric.
[0075] Scanning electron microscopy images of original polyester fabric, conjugated Schiff base single-coated polyester fabric, and Cu9S5 / conjugated Schiff base double-coated polyester fabric are shown in Figure 2. Figure 1 As shown, the surface of the polyester fabric becomes rough after treatment; after coating with conjugated Schiff base, the conjugated Schiff base adheres to the polyester fabric and flocculent substances are deposited; the Cu9S5 coating is evenly distributed in the polyester fabric coated with Cu9S5 and conjugated Schiff base.
[0076] EDS images of original polyester fabric, conjugated Schiff base single-coated polyester fabric, and Cu9S5 / conjugated Schiff base double-coated polyester fabric are shown in Figure 2. Figure 2 , 3 As shown, Figure 2 , 3 It can be seen that the double-coated fabric has more Cu and S elements than the single-coated fabric, from which it can be inferred that the Cu9S5 conductive coating was successfully prepared on the polyester fabric.
[0077] X-ray diffraction pattern Figure 4 As shown in the figure, the main diffraction peaks are similar in the range of 15°-30°, and the conjugated Schiff base has not crystallized on the polyester fabric. At the same time, by comparing the intensity of the diffraction peaks of the two, it is found that the single-coated polyester fabric has a slightly stronger peak intensity, which may be because the conjugated Schiff base coating enhances the rigidity of the overall crystalline structure of the polyester fabric. Diffraction peaks appear at angles of 17.2°, 22.8° and 25.7°. These three diffraction peaks are characteristic peaks of polyester fabric.
[0078] The X-ray diffraction pattern of the Cu9S5 / conjugated Schiff base double-coated polyester fabric was compared with the Cu9S5 standard card (PDF47-1748), and the characteristic diffraction peaks at angles of 37.88° and 47.18° were consistent with the standard card, proving that the Cu9S5 coating was successfully prepared.
[0079] like Figure 5In the infrared spectrum shown in the figure, the conjugated Schiff base single-coated polyester fabric has a wavelength of 3435 cm -1 The characteristic absorption peak of -OH in polyester fabric appears at 2927cm -1 The absorption peak of CH group is at 1716cm-1, and the C=O stretching vibration in polyester fabric appears at 1243cm-1; -1 1097cm -1 At 727cm -1 The absorption peak at is due to the characteristic CH bond of the benzene ring. The infrared spectrum of Cu9S5 / conjugated Schiff base double-coated polyester fabric also has characteristic peaks at the corresponding positions, but the positions of the peaks are slightly shifted and the intensity changes.
[0080] Example 2
[0081] This embodiment provides a method for preparing Cu9S5 / polyaniline double-coated cotton fabric.
[0082] 1) Preparation of polyaniline coating:
[0083] By adopting the in-situ polymerization method, aniline monomer was dissolved in 50 mL of 1.25 mol / L sulfuric acid, the concentration of aniline monomer was 0.5 mol / L, and 50 mL of distilled water was used to prepare ammonium persulfate solution, the concentration of ammonium persulfate was 0.375 mol / L;
[0084] Mix the aniline sulfate solution and the ammonium persulfate solution and stir evenly;
[0085] When the solution starts to turn blue, put the original cotton fabric into the solution, control the bath ratio to 1:50, and shake the reaction at room temperature for 12 hours;
[0086] The cotton fabric was taken out, thoroughly cleaned with distilled water and dried in an oven to obtain a polyaniline single-coated cotton fabric.
[0087] 2) Preparation of Cu9S5 coating:
[0088] Mix 6g / L copper sulfate solution and 7.2g / L sodium thiosulfate solution and stir evenly;
[0089] The pH value was adjusted to 2 with sulfuric acid, and the bath ratio was controlled to 1:160. The polyaniline / cotton fabric was placed in the solution, and the temperature of the constant temperature oscillator was adjusted to 65°C. The fabric was placed in the solution for reaction. When the temperature reached 65°C, the timing was started and the reaction lasted for 55 minutes.
[0090] After the reaction, the sample was taken out, thoroughly washed with distilled water and dried in an oven to obtain Cu9S5 / conjugated Schiff base double-coated cotton fabric.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 2 is that step 2) is omitted, and the remaining steps are referred to Example 2 to prepare a polyaniline single-coated cotton fabric.
[0093] Scanning electron microscopy images of original cotton fabric, polyaniline single-coated cotton fabric, and Cu9S5 / polyaniline double-coated cotton fabric are shown in Figure 2. Figure 6 As shown, the original cotton fabric fibers are in the shape of longitudinal flat bands. Due to the formation of the polyaniline coating, a flake-like distribution is formed on the fiber surface. The polyaniline covers the fiber surface more evenly. It can be observed that Cu9S5 is deposited more on the fabric and the coating is more uniform.
[0094] Figure 7 , 8 The EDS images of polyaniline single-coated cotton fabric and Cu9S5 / polyaniline double-coated cotton fabric. Figure 7 , 8 It can be seen that the elements on the fabric are distributed evenly. Nitrogen exists on the polyaniline / cotton fabric, and sulfur and copper exist on the Cu9S5 / polyaniline double-coated cotton fabric, indicating that the polyaniline coating was successfully prepared on the cotton fabric, and the Cu9S5 coating was successfully prepared on this basis.
[0095] Fig. 9 The XRD diagrams of the original cotton fabric, the polyaniline single-coated cotton fabric, and the Cu9S5 / polyaniline double-coated cotton fabric are shown in Figure 2. In the X-ray diffraction peak curve of the original cotton fabric, the main diffraction peaks of the cotton fabric are shown at angles of 14.9°, 16.7°, 22.8°, and 34.3°. The XRD curve of the polyaniline single-coated cotton fabric is similar to the XRD curve of the original cotton fabric, because the polyaniline is not crystallized on the cotton fabric. The X-ray diffraction curve of the Cu9S5 / polyaniline double-coated cotton fabric is compared with the Cu9S5 standard card (card number: 47-1748). Cu9S5 has characteristic diffraction peaks at angles of 29.3°, 32.1°, and 47.7°, which is consistent with the Cu9S5 standard card, proving that the Cu9S5 coating is successfully prepared.
[0096] The infrared spectra of original cotton fabric, polyaniline single-coated cotton fabric, and Cu9S5 / polyaniline double-coated cotton fabric are shown in Figure 2. Fig.10 As shown. 3283cm -1 2923cm is the stretching vibration of OH in cotton fiber; -1 The CH stretching vibration in cotton fiber; 1423cm -1 The C-H2 bending vibration in cotton fiber is at 3336cm -1 The stretching vibration of secondary amine NH in the polyaniline molecular chain appears at 1585cm- 1 and 1498cm-1 The stretching vibration of C=C in the polyaniline molecular chain appears at 1309cm -1 and 1108cm -1 The CN stretching vibration of the polyaniline molecular chain appears at 699cm -1 The out-of-plane bending vibration of C=C in the polyaniline molecular chain appears at 483cm. This proves that the cotton fabric surface is successfully covered by polyaniline. In the infrared curve of the double-coated cotton fabric, the formation of Cu9S5 covers the characteristic peaks of cotton and polyaniline, 483cm -1 and 1223cm -1 The characteristic absorption vibration peak of copper appears at , indicating the successful preparation of Cu9S5 on the polyaniline coating.
[0097] The limiting oxygen indexes of the original cotton fabric, the polyaniline single-coated cotton fabric, and the Cu9S5 / polyaniline cotton fabric were measured. The limiting oxygen indexes of the three were 17%, 19.2%, and 21.4%. Polyaniline and Cu9S5 have flame retardant properties, and they form a coating on the cotton fabric, thereby making the cotton fabric have a better flame retardant effect.
[0098] Example 3
[0099] This embodiment provides a method for preparing Cu9S5 / polypyrrole double-coated cotton fabric.
[0100] 1) Preparation of polypyrrole coating:
[0101] Place a piece of raw cotton fabric (about 5 cm × 5 cm) in a 10 cm diameter Petri dish, add 0.36 mol / L ferric chloride (FeCl3) and 0.36 mol / L sodium 5-sulfosalicylate (NaSSA) solution to just immerse the fabric, and then place the Petri dish in a freezer for 30 min;
[0102] An equal volume of 0.4 mol / L cyclohexane solution of pyrrole monomer was poured into the above-mentioned culture dish. After the cyclohexane solution was frozen, the culture dish was kept static at 0-5°C for 12 hours and then taken out. The sample was repeatedly washed with distilled water and ethanol, respectively, and vacuum dried at 60°C for 12 hours to obtain a polypyrrole single-coated cotton fabric.
[0103] 2) Preparation of Cu9S5 coating:
[0104] Control the bath ratio to 1:80, mix 6g / L copper sulfate solution and 7.2g / L sodium thiosulfate solution, and stir evenly;
[0105] The pH value was adjusted to 2 with sulfuric acid, and the polypyrrole single-coated cotton fabric was placed in the solution. The temperature of the constant temperature oscillator was adjusted to 65°C. When the temperature rose to 65°C, the reaction was started and the timing was 25 minutes. When the time was up, the sample was taken out, washed thoroughly with deionized water, and dried in an oven to obtain the Cu9S5 / polypyrrole double-coated cotton fabric.
[0106] Comparative Example 3
[0107] The difference between this comparative example and Example 3 is that step 2) is omitted, and the remaining steps are referred to Example 3 to prepare a polypyrrole single-coated cotton fabric.
[0108] The infrared spectra of original cotton fabric, polypyrrole single-coated cotton fabric, and Cu9S5 / polypyrrole double-coated cotton fabric are shown in Figure 2. Fig.11 As shown. 3340cm -1 2902cm is the stretching vibration of OH in cotton fiber; -1 1432cm is the stretching vibration of CH in cotton fiber; -1 The C-H2 bending vibration in cotton fiber. 1531cm -1 Represents the stretching vibration of the C=C bond in the polypyrrole skeleton, 1438 cm -1 Represents skeleton light band, 1292cm -1 is the stretching vibration of the C―C bond in the pyrrole ring, 1141 cm -1 is the antisymmetric in-plane bending vibration of C―H bond, 1081cm -1 and 1018cm -1 The double peak at 956cm represents the symmetrical in-plane bending vibration of the C-H bond when forming a bipolaron and a polaron. -1 It represents the deformation vibration of the pyrrole ring when a polaron is formed. The infrared spectrum of Cu9S5 / polypyrrole double-coated cotton fabric also shows characteristic peaks at the corresponding positions, but the positions of the peaks have shifted slightly and the intensity has changed. This is because during the complex process between copper sulfide and polypyrrole molecules, their interaction reduces the electron cloud density on the polypyrrole molecular chain and reduces the interatomic force constant.
[0109] like Fig.12 As shown, the XRD pattern of the polypyrrole single-coated cotton fabric is similar to the XRD pattern of the original cotton fabric. The reason is that polypyrrole does not crystallize on the cotton fabric. The original cotton fabric presents four main diffraction peaks at angles of 14.0°, 16.7°, 22.7° and 34.1°, respectively. Cu9S5 has characteristic diffraction peaks at angles of 46.17°, 32.17° and 27.77°, which is consistent with the Cu9S5 standard card (card number: 47-1748), indicating that the Cu9S5 coating was successfully prepared.
[0110] Scanning electron microscopy images of original cotton fabric, polypyrrole single-coated cotton fabric, and Cu9S5 / polypyrrole double-coated cotton fabric are shown in Figure 2. Fig.13 As shown in the figure, the raw cotton fiber presents a longitudinal flat ribbon shape. Due to the formation of the polypyrrole conductive coating, the fiber surface forms a sheet-like distribution. The polypyrrole conductive layer is first formed on the cotton fiber surface, that is, the lone pair of nitrogen electrons are introduced, so that copper ions can be adsorbed. The amount of polypyrrole covering the fiber surface is large, and it can be observed that the deposition of Cu9S5 on the fabric is also large and the coating is relatively uniform.
[0111] EDS images of Cu9S5 / polypyrrole double-coated cotton fabrics are shown in Figure 2. Fig.14 The upper left corner is a scanning electron microscope image of a certain area of Cu9S5 / polypyrrole double-coated cotton fabric, followed by mapping images of five elements, namely N, O, S, Cu, and C. Compared with the scanning electron microscope image of the polypyrrole single-coated cotton fabric, there is an additional copper element, indicating that Cu9S5 has been successfully loaded on the polypyrrole coating, and the Cu9S5 coated cotton fabric surface is relatively evenly distributed.
[0112] The limiting oxygen index of original cotton fabric, polypyrrole single-coated cotton fabric and Cu9S5 / polypyrrole double-coated cotton fabric was measured. The limiting oxygen index of original cotton fabric was 17.1%, the limiting oxygen index of polypyrrole single-coated cotton fabric was improved to 25.3%, and the limiting oxygen index of Cu9S5 / polypyrrole double-coated cotton fabric was 21.4%, which was lower than that of polypyrrole single-coated cotton fabric, but still increased compared with original cotton fabric.
[0113] The comparative results of the conductivity test of the fabrics prepared in Examples 1 to 3, Comparative Examples 1 to 3 and the original fabric are shown in Table 1.
[0114] Table 1 Comparison of antistatic properties of different fabrics
[0115]
[0116]
[0117] It can be seen from Table 1 that after coating with organic coating and Cu9S5 coating, the electrostatic voltage half-life of the fabric is significantly reduced. The half-life of single-coated and double-coated fabrics is less than 1s, reaching the Class A standard, with good antistatic performance. The organic coating and Cu9S5 coating synergistically reduce the electrostatic voltage half-life of the fabric and enhance the conductive properties of the fabric.
[0118] The comparative results of the anti-ultraviolet performance of the fabrics prepared in Examples 1 to 3, Comparative Examples 1 to 3 and the original fabric are shown in Table 2.
[0119] Table 2 UV resistance test results
[0120] sample UVA transmittance (%) UVB transmittance (%) Protection Factor (UPF) Raw polyester fabric 9.84 11.35 23.1 Comparative Example 1 2.46 1.58 55.76 Example 1 1.13 1.02 92.68 Raw cotton fabric 14.72 8.53 9.13 Comparative Example 2 1.79 1.8 55.55 Example 2 1.26 1.24 79.47 Comparative Example 3 0.42 0.42 240.47 Example 3 0.08 0.07 1839.49 UV protection product standards <5 — >40
[0121] As shown in Table 2, the anti-ultraviolet performance of polyester fabric and cotton fabric is poor, which does not meet the standards of anti-ultraviolet products. However, after being coated with three organic substances and Cu9S5, the fabric has excellent anti-ultraviolet performance. The UPF value of single coating and double coating is greater than 40, and the UVA transmittance is less than 5%, which meets the standards of anti-ultraviolet products. Among them, the anti-ultraviolet performance of Cu9S5 / polypyrrole double-coated cotton fabric is the best.
[0122] The resistivity measurement results of the fabrics prepared in Examples 1 to 3, Comparative Examples 1 to 3 and the original fabric are shown in Table 3.
[0123] Table 3 Test results of resistivity of different fabrics
[0124] sample Average resistivity (Ω·m) Comparative Example 1 — Example 1 18.5 Comparative Example 2 2.04 Example 2 0.99 Comparative Example 3 0.46 Example 3 0.1
[0125] As shown in Table 3, the conjugated Schiff base single-coated polyester fabric exceeds the measurement range, and the resistivity is significantly reduced after coating with Cu9S5; the resistance of the original cotton fabric exceeds the range of the instrument and cannot be measured by the instrument. The resistivity of the Cu9S5 / polyaniline double-coated cotton fabric is significantly lower than that of the polyaniline single-coated cotton fabric; the resistance value of the polypyrrole single-coated cotton fabric is very small, and the conductive property of polypyrrole is very good. After coating with Cu9S5, its resistance value is significantly reduced. The Cu9S5 coating significantly reduces the resistivity of the fabric, making the fabric have excellent conductive properties.
[0126] Comparative Example 4
[0127] The difference between this comparative example and Example 1 is that the concentrations of p-phenylenediamine and glyoxal are adjusted, and other conditions are the same, to prepare conjugated Schiff base single-coated polyester fabrics under different conditions, and the weight gain comparison thereof is shown in Table 4.
[0128] Table 4 Comparison of weight gain of conjugated Schiff base single-coated polyester fabrics under different conditions
[0129] p-phenylenediamine mol / L Glyoxal mol / L Weight gain% 0.03 0.03 4.36 0.01 0.01 1.24 0.06 0.06 2.73 0.09 0.09 1.12
[0130] As shown in Table 4, when the concentrations of p-phenylenediamine and glyoxal are both 0.03 mol / L, the weight gain rate is the highest, which is 4.36%. When the concentration of p-phenylenediamine is greater than 0.03 mol / L, precipitation begins to form in the solution, and the amount of precipitation increases with the increase of concentration. As the concentration increases, p-phenylenediamine and glyoxal will react chemically to produce precipitation.
[0131] Comparative Example 5
[0132] The difference between this comparative example and Example 1 is that the reaction temperature of the conjugated Schiff base single coating preparation process is adjusted to 65°C and 85°C, and other conditions are the same. Conjugated Schiff base single coating polyester fabrics under different conditions are prepared, and their weight gain comparison is shown in Table 5.
[0133] Table 5 Comparison of weight gain of conjugated Schiff base single-coated polyester fabrics under different conditions
[0134]
[0135] It can be seen from Table 5 that the weight gain rate is the highest when the reaction temperature is 65°C, which is 4.36%.
[0136] Comparative Example 6
[0137] The difference between this comparative example and Example 1 is that the concentrations of copper sulfate and copper thiosulfate and the reaction time are adjusted, and other conditions are the same, and Cu9S5 / conjugated Schiff base double-coated polyester fabrics under different conditions are prepared, and the weight gain comparison is shown in Table 6.
[0138] Table 6 Comparison of weight gain of Cu9S5 / conjugated Schiff base double-coated polyester fabrics under different conditions
[0139] Copper sulfate g / L Sodium thiosulfate g / L Reaction time min Weight gain% 6 7.2 65 3.4 3 3.6 35 0.4 7.5 9 35 1.5 9 10.8 35 1.4
[0140] It can be seen from Table 6 that there are differences in the weight gain rates of the prepared double-coated polyester fabrics. The Cu9S5 / conjugated Schiff base double-coated polyester fabric obtained under the conditions of Example 1 has the highest weight gain rate of 3.4%.
[0141] Comparative Example 7
[0142] The difference between this comparative example and Example 1 is that the reaction time of the Cu9S5 coating preparation process is adjusted, and other conditions are the same, and Cu9S5 / conjugated Schiff base double-coated polyester fabrics under different conditions are prepared, and the weight gain comparison is shown in Table 7.
[0143] Table 7 Comparison of weight gain of Cu9S5 / conjugated Schiff base double-coated polyester fabrics under different conditions
[0144]
[0145]
[0146] It can be seen from Table 7 that there are differences in the weight gain rates of the prepared double-coated polyester fabrics. The Cu9S5 / conjugated Schiff base double-coated polyester fabric obtained in Example 1 has the highest weight gain rate of 3.4%.
[0147] Fig.15The resistance values of Cu9S5 / conjugated Schiff base double-coated fabrics with different weight gain rates are shown in Table 1. The resistance value of the conjugated Schiff base single-coated polyester fabric is very large and has exceeded the measurement range. The resistance value of the polyester fabric changes significantly after being coated with Cu9S5, and as the amount of Cu9S5 coated increases, the resistance value gradually decreases. The better the conductivity of Cu9S5, the greater the conductivity of polyester. The fabric of Example 1 has the lowest resistivity and the best conductivity.
[0148] Comparative Example 8
[0149] The difference between this comparative example and Example 2 is that the concentrations of aniline, ammonium persulfate and sulfuric acid are adjusted, and other conditions are the same, to prepare polyaniline single-coated cotton fabrics under different conditions, and the weight gain comparison thereof is shown in Table 8.
[0150] Table 8 Weight gain of polyaniline single-coated cotton fabric under different conditions
[0151] Aniline concentration mol / L Ammonium persulfate concentration mol / L Sulfuric acid concentration mol / L Weight gain% 0.5 0.375 1.25 2.04 0.2 0.15 0.5 0.73 0.4 0.3 1 1.5 0.6 0.45 1.5 2.67 0.5 0.375 1.5 1.93
[0152] It can be seen from Table 8 that although the weight gain of the sample is the largest when the concentration of aniline is 0.6 mol / L, the concentration of ammonium persulfate is 0.45 mol / L, and the concentration of sulfuric acid is 1.5 mol / L, the polyaniline coating on the surface of the cotton fabric is not uniform and has poor uniformity. The weight gain under the conditions of Example 2 is higher, at 2.04%, and the uniformity is better.
[0153] Comparative Example 9
[0154] The difference between this comparative example and Example 2 is that during the preparation of the polyaniline single-coated cotton fabric, the bath ratio is adjusted to 1:100, and other conditions are the same. The polyaniline single-coated cotton fabrics under different conditions are prepared, and their weight gain comparisons are shown in Table 9.
[0155] Table 9 Weight gain of polyaniline single-coated cotton fabric under different conditions
[0156]
[0157] It can be seen from Table 9 that the weight gain is higher when the bath ratio is 1:50, which is 2.04%.
[0158] Comparative Example 10
[0159] The difference between this comparative example and Example 2 is that the aniline concentration is adjusted to 1 mol / L, the ammonium persulfate concentration is 0.75 mol / L, and the sulfuric acid concentration is 2.5 mol / L. The other conditions are the same as those in Example 2. After the aniline sulfate solution and the ammonium persulfate solution are mixed for a period of time, the solution gradually solidifies, the reaction solution is in a saturated state, and the preparation of the polyaniline coating fails.
[0160] Comparative Example 11
[0161] The difference between this comparative example and Example 2 is that the reaction time of the Cu9S5 coating preparation process is adjusted, and other conditions are the same, and the Cu9S5 / polyaniline double-coated cotton fabrics under different conditions are prepared, and the weight gain comparison is shown in Table 10.
[0162] Table 10 Comparison of weight gain of Cu9S5 / polyaniline double-coated cotton fabric under different conditions
[0163]
[0164] It can be seen from Table 10 that the weight gain rate is the highest when the reaction time is 55 min, which is 14.6%.
[0165] Comparative Example 12
[0166] The difference between this comparative example and Example 3 is that the reaction time for preparing the Cu9S5 coating is adjusted to 35 min and 45 min, and the other conditions are the same, as shown in Table 11.
[0167] Table 11 Comparison of weight gain of Cu9S5 / polypyrrole double-coated cotton fabrics under different conditions
[0168]
[0169] It can be seen from Table 11 that the Cu9S5 / polypyrrole double-coated cotton fabric prepared in Example 3 has the highest weight gain rate of 4.88%.
[0170] Comparative Example 13
[0171] The difference between this comparative example and Example 3 is that the reaction temperature for preparing the Cu9S5 coating is adjusted. Other conditions are the same, and Cu9S5 / polypyrrole double-coated cotton fabrics under different conditions are prepared. The comparison of their weight gain rates is shown in Table 12.
[0172] Table 12 Comparison of weight gain of Cu9S5 / polypyrrole double-coated cotton fabrics under different conditions
[0173]
[0174] It can be seen from Table 12 that when the temperature is 65°C, the weight gain rate of Cu9S5 / polypyrrole double-coated cotton fabric is the highest, which is 4.88%.
[0175] In summary, the double-coated fabric prepared by the present invention meets the requirements of anti-ultraviolet products (UPF value is greater than 40, and UVA transmittance is less than 5%), and the antistatic performance reaches Class A. Cu9S5, conjugated Schiff base, polyaniline, and polypyrrole synergistically improve the conductivity of cotton and polyester fabrics, improve the antistatic effect and anti-ultraviolet performance, and achieve a higher weight gain rate of organic matter and Cu9S5 by optimizing the preparation conditions of organic matter and Cu9S5 coating.
[0176] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an antistatic fabric based on a Cu9S5 / organic double coating, characterized in that: include, In-situ preparation of an organic coating on the fabric to obtain an organic single-coated fabric; The copper sulfate solution and the sodium thiosulfate solution are uniformly mixed to obtain a mixed solution I; The organic single-coated fabric is placed in the mixed solution I, and after constant temperature reaction, it is taken out, thoroughly washed, and dried to obtain the Cu9S5 / organic double-coated fabric; Wherein, the organic coating includes one of a conjugated Schiff base coating, a polyaniline coating and a polypyrrole coating.
2. The method for preparing an antistatic fabric based on a Cu9S5 / organic double coating as claimed in claim 1, characterized in that: The fabric comprises one of cotton fabric and polyester fabric.
3. The method for preparing an antistatic fabric based on a Cu9S5 / organic double coating as claimed in claim 1, characterized in that: The preparation method of the conjugated Schiff base coating comprises: The fabric pretreated with caustic soda solution is immersed in 0.01-0.09 mol / L p-phenylenediamine ethanol solution and reacted at 20-25° C. for 2-2.5 hours; Add glyoxal solution of the same concentration as the p-phenylenediamine ethanol solution, stir evenly, and shake at 65-85° C. for 6-7 hours to form a conjugated Schiff base coating on the fabric.
4. The method for preparing an antistatic fabric based on a Cu9S5 / organic double coating as claimed in claim 1, characterized in that: The preparation method of the polyaniline coating comprises: Aniline sulfuric acid solution with an aniline monomer concentration of 0.2 to 0.6 mol / L and ammonium persulfate solution with a concentration of 0.15 to 1.5 mol / L are mixed evenly; When the solution starts to turn blue, add the fabric, control the bath ratio to 1:50-1:100, and shake at room temperature for 10-12 hours; The fabric is taken out, thoroughly washed and dried, thereby forming a polyaniline coating on the fabric.
5. The method for preparing an antistatic fabric based on a Cu9S5 / organic double coating as claimed in claim 1, characterized in that: The preparation method of the polypyrrole coating comprises: The fabric was immersed in 0.3-0.36 mol / L FeCl3 solution and 0.3-0.36 mol / L sodium 5-sulfosalicylate solution and frozen for 30-50 min; An equal volume of 0.25-0.55 mol / L cyclohexane solution of pyrrole monomer is added, and after the cyclohexane solution is frozen, it is kept statically at 0-5°C for 10-12 hours, then taken out, repeatedly washed with distilled water and ethanol, respectively, and vacuum dried to form a polypyrrole coating on the fabric.
6. The method for preparing an antistatic fabric based on a Cu9S5 / organic double coating as claimed in claim 1, characterized in that: The bath ratio of the organic single-coated fabric to the mixed solution I is 1:80-160, wherein the pH value of the mixed solution I is 2-2.
5.
7. The method for preparing an antistatic fabric based on a Cu9S5 / organic double coating as claimed in claim 1, characterized in that: The concentration of the copper sulfate solution is 3-9 g / L, and the concentration of the copper thiosulfate solution is 3.6-10.8 g / L.
8. The method for preparing an antistatic fabric based on a Cu9S5 / organic double coating as claimed in claim 1, characterized in that: The reaction temperature of the isothermal reaction is 55-85° C., and the reaction time is 25-95 min.
9. Antistatic fabric based on Cu9S5 / organic double coating prepared by the preparation method according to any one of claims 1 to 8.
10. The antistatic fabric based on Cu9S5 / organic double coating as claimed in claim 9, characterized in that: The UPF value of the antistatic fabric is greater than 40, the UVA transmittance is less than 5%, and the antistatic performance reaches Class A.